DESAIN RULES UNTUK TRANSFORMASI SINTAKS RDF (TEXT) KE RDF BERBASIS GRAFIK DALAM SEMANTIC WEB - Prapanca, Aditya (Institute of Research and Community Outreach - Petra Christian University, 2008)
Semantic Web is a branch of field that provides infrastructure for the exchange of information from various resources based on the combined meaning contained in the information exchanged and the relationship between one particular meaning to another. In the semantic web, there are semantics, which connect a set of data that has a meaning which allows occurrence of the exchange of information. The aim of this study is to make rules used in the process of transformation from the RDF document to be RDF graph, the data model so that it can provide semantic meaning in a web of visual content (graphic). By using these rules, a case can be made based graphical tool that can help the designer in created the data model. The results are models form of graphical data input from text-based documents RDF. For the transformation process, starting with a separate document, then taken sequentially the object, and then take the attributes of the object, and the last search for the relationship of each object that is.